Essential Oil Essential Oil Analysis of Some Plants - Demir, hulya; Oyman, Busra Umut (Jour Med Resh and Health Sci, 2022)
Background: Essential oils are composed of terpenic or nonterpenic volatile compounds. They can be found in the forms of alcohol, acid, ester, epoxide, aldehyde, ketone, amine, and sulfide. The aim in the present study was to evaluate the chemical content of Ocimum basilicum, Melissa officinalis, Lavandula officinalis, Mentha piperita L., Salvia officinalisL., and Thymus vulgaris L. essential oils. Methods: Essential oil samples of the plants were obtained by 4-hour water distillation in the Clevenger apparatus. After boiling started, distillation continued for 4 hours until the flow of liquid finished. The volatile oils were analyzed using a Shimadzu QP2010-Plus model GC/MS. The essential oil components were characterized using electronic libraries Results: The main components of Ocimum basilicum were 53% 1,6-octadien-3-ol, The main components of Melissa officinalis were 26% d-limonene, The main components of Lavandula officinalis were 42.07% 1,6-octadien-3-ol, The main components of Mentha piperita L. were eucalyptol (cineole), The main components of Salvia officinalis L. were ?-pinene, The main components of Thymus vulgaris L. were o-cymene. Conclusions: Essential oils are also important in protecting foods due to their effects in treating bacterial infections, fungal diseases, wounds, burns, and acne.